Abdominal venous thromboses: detection of the JAK2 p.V617F mutation by next-generation ultradeep sequencing—A prevalence study of patients in Mecklenburg-West Pomerania (2017–2021) - Henze, Larissa; Grunwald, Luise; Felser, Sabine; Witte, Maria; Grosse-Thie, Christina; Roolf, Catrin; Murua Escobar, Hugo; Junghanss, Christian (Frontiers in Medicine, 2024)
Background Abdominal venous thromboses are rare thrombotic events with heterogeneous etiologies. They are related to myeloproliferative neoplasms (MPNs) in some patients and can occur as first signs of the disease. MPNs are characterized by mutations in the genes of Janus kinase 2 (JAK2), myeloproliferative leukemia virus oncogene (MPL), and calreticulin (CALR). Methods Within the prospective trial “Prevalence of JAK2 mutations in patients with abdominal venous thromboses” (JAK2 MV study; German Clinical Trials Register: DRKS00026943), the peripheral blood of patients with abdominal venous thromboses in Mecklenburg-West Pomerania, a federal state located in north-east Germany, was analyzed by next-generation ultradeep sequencing for MPN-associated mutations. Clinical characteristics and blood cell counts were also of interest. The primary endpoint was the detection of the mutation JAK2 p.V617F. Secondary endpoints were the detection of other acquired variants of JAK2, as well as MPL and CALR. Results A total of 68 patients with abdominal venous thromboses were included from February 2017 to January 2021, with splanchnic veins affected in 65 patients. The mutation JAK2 p.V617F was present in 13 patients (19%), with four patients showing low variant allele frequencies (VAF 0.1% to 1.9%). The time interval from the thrombotic event to analysis was longer for patients with the mutation. The mutation MPL p.W515R was detected in three cases, all of them with low VAF. One patient among them had a concurrent mutation of JAK2 p.V617F. The mutations CALR type I or type II were not found. Discussion By analyzing peripheral blood for the mutation JAK2 p.V617F, an important cause of these rare thrombotic events can be identified. The development of a diagnostic workup with next-generation ultradeep sequencing for the analysis of the JAK2 p.V617F mutation and further mutations has the potential to better understand the etiology of abdominal venous thromboses in individual patients in regional clinical care, as abdominal venous thromboses are diagnosed by various medical disciplines.